ACCOUNTING FOR NO-PAR STOCK ISSUES. - Hornberger, D. J. (The Accounting Review, 1929)
Abstract Considerable attention has been given during the past decade to methods of valuing no-par stocks for the purpose of financial statements. Very little, however, has appeared as to actual methods in use and the reasons supporting them. To obtain reliable information on these points, an analysis of the methods of valuing no-par stock issues as shown on the balance sheets of nine hundred and fifty-six corporations has recently been made. These studies include practically all corporations whose no-par issues are listed on the exchanges, and a number of non-listed companies. Twelve hundred and thirteen no-par stock issues were included in the studies, of which 972 were common stocks and 241 preferred issues. The studies were divided roughly between utilities and industrials, 614 of the former and 599 of the latter. The conclusion drawn was that there are five basic method. of accounting for no-par issues, which are, in the order of their importance, paid-in or equivalent value, stated value, net worth at date of balance sheet, net worth at date of incorporation or of refinancing, liquidation value.